PRODUKTIVITAS DUCKWEED (Lemna sp.) SEBAGAI ALTERNATIF HIJAUAN YANG DIBERI PUPUK ORGANIK CAIR (POC) MEGARHIZO - Priya Citra Haryanto; Catur Suci Purwati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
The main challenge in the livestock sector today is soaring production costs due to the limited availability of conventional forage. This study aims to analyze and evaluate the effectiveness of Megarhizo Liquid Organic Fertilizer (POC) on the productivity and morphological characteristics of duckweed (Lemna sp.) as a candidate for alternative feed. Specifically, this study aimed to map plant responses, including fresh weight, dry weight, leaf width, and root length, as well as their impact on the stability of the growing medium's water quality. This experiment was designed using a Completely Randomized Design (CRD) consisting of four POC dosage levels (P0: 0 ml, P1: 15 ml, P2: 20 ml, and P3: 25 ml per 10 liters of water) with four replications. The data analysis results showed that the application of POC had a significant effect (P < 0.05) in improving the quality of the cultivation environment, indicated by a decrease in water temperature and a neutralization of the pH level from alkaline conditions (9.17) to the optimal range (7.79). However, the addition of nutrients through liquid organic fertilizer (POC) did not have a significant impact (P > 0.05) on all physical plant growth parameters. Among all treatments, the P1 dose (15 ml/10L) was identified as the most efficient concentration because it produced the maximum average root length (25.89 cm) and dry matter weight (4.71 grams) compared to other doses. This study concluded that although it was not able to significantly increase biomass in a short time, the Megarhizo liquid organic fertilizer played a crucial role in creating more ideal growing media conditions for the sustainability of duckweed cultivation as a source of animal feed.